2012
DOI: 10.1002/chem.201201287
|View full text |Cite
|
Sign up to set email alerts
|

Borophosphonate Cages: Easily Accessible and Constitutionally Dynamic Heterocubane Scaffolds

Abstract: A versatile and experimentally facile procedure for the synthesis of borophosphonate cages of the general formula [tBuPO(3)BR'](4) is described. The method involves heating of tert-butylphosphonic acid with a boronic acid in toluene to give borophosphonates in [4+4] condensation reactions. The products display a heterocubane structure with bent P-O-B bridges as evidenced by crystallographic analyses. Scrambling experiments show that the borophosphonate cages are constitutionally dynamic scaffolds with exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…According to mass spectrometry, this byproduct has the formula [EtOPO 3 BPh] 4 . It appears likely that this compound has a heterocubane structure as observed for borophosphonates 10,11. Attempts to isolate the side product in pure form were not successful.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…According to mass spectrometry, this byproduct has the formula [EtOPO 3 BPh] 4 . It appears likely that this compound has a heterocubane structure as observed for borophosphonates 10,11. Attempts to isolate the side product in pure form were not successful.…”
Section: Resultsmentioning
confidence: 82%
“…Over the last years, our group has investigated the synthesis of molecular and polymeric nanostructures by simple polycondensation reactions involving boronic acids 8,9. In the course of this work, we found that it was possible to obtain heterocubic borophosphonates in [4+4] condensation reactions from tert ‐butylphosphonic acid and boronic acids 10,11. We reasoned that a similar approach might be suited for the formation of soluble borophosphates.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of shape-persistent organic cage compounds, applying dynamic covalent chemistry (DCC) has developed in recent years tremendously fast and enabled the access of a large variety of defined molecular structures of different sizes, geometries and functions. [1][2][3][4][5][6] Although a few examples of boronic ester cages, or those based on disulphide formation or other DCC reactions are known, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] no doubt, the vast majority of shape-persistent organic cages is relying on the use of multiple imine condensation reactions, 1 which bear the advantage to be transformed further to convert these to chemically robust cages, [27][28][29][30][31] which is for the other type of DCC reactions difficult or even impossible. 32 Among those imine cages, shapes, such as trigonal prisms, [33][34][35] tetrahedra, [36][37][38][39] truncated tetrahedra, 40,41 cubes, [42][43]…”
Section: Introductionmentioning
confidence: 99%
“…Yet if the group itself is not directly ionized and is not in proximity of the suspected site of ionization, it may be preserved. Azidecontaining analytes (compounds [34][35][36], are a good illustration of this hypothesis. Typically, azides show strong [M+H -N 2 ] + loss [45], as well as, occasionally, loss of N 3 species (see APPI mass spectrum of compound 35 in Supplementary Figure S2).…”
Section: Reactive Functional Groupsmentioning
confidence: 99%
“…However, this is of particular interest to researchers in areas such as supramolecular chemistry [71,72], drug delivery via nanomaterials [73,74], solar cells development [75][76][77], or vaccine adjuvants [78,79], as oftentimes compounds of interest lack basic/acidic sites, may be non-polar, and do not ionize well with ESI. Here, a selection of such analytes investigated in our institute is given, compiled from recently published research articles [35,37,[80][81][82][83]. Notably, APPI was able to ionize analytes near or above 3 kDa, with several selected complexes showcasing the variation in underlying chemical diversity demonstrated in compounds A-H, which also include metal complexes (see Figure 5 for compound structure and Supplementary Figure S2 for associated APPI mass spectra).…”
Section: Upper Mass Limit On Appi Ionizationmentioning
confidence: 99%